(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2021)
Endotoxins may play an important role in the development of various symptoms in occupational environments where exposure to bacteria is prevalent. The standard analytical method for endotoxin is the Limulus amebocyte lysate (LAL) assay. The Gel-Clot method is one of the simplest, least expensive and has good sensitivity technique of LAL assay. In this study volumetric sampling technique has been applied for enumeration and quantification of airborne viable counts Endotoxin from indoor and outdoor air of school. An Endotoxin (Pyrogen)-free filter cassette with PTFE membrane filter has been used for air sampling. 240L air volume has been sampled for sampling of Endotoxin at the rate of 4LPM. Extraction of Endotoxins from the collected air samples has been done in Endotoxin-free water to avoid the evolving of false positive results during assay. Assay results indicate that Endotoxin level (EUm3) has been higher in indoor air than outdoor air. It is an indicator inside source of Endotoxins.